Balkan and South Slavic enclaves in Italy : languages, dialects and identities - Kahl, Thede, 1971- (Cambridge Scholars Publishing, 2018)
This volume is a collection of new writings dealing with some of the Balkan linguistic varieties spoken in north-eastern, central and southern Italy. It brings together twenty-two papers, some of which investigate the mutual influences between each of these Balkan and South Slavic language varieties and their neighbouring Italian dialects. Other contributions study common tendencies which do not just pertain to local contacts, but which are of greater significance for the history of linguistic and cultural contacts in Italy. All of the chapters here present new empirical findings and reflect t.